2014
DOI: 10.1063/1.4863600
|View full text |Cite
|
Sign up to set email alerts
|

Fast and slow stress evolution mechanisms during interruptions of Volmer-Weber growth

Abstract: The evolution of mechanical stress during Volmer-Weber growth of thin films is complex, often including a reversible stress evolution during interruptions of film deposition. The underlying mechanism for stress evolution during growth interruptions has been extensively debated, but remains unclear. In this work, in situ measurements of stress evolution during growth interruptions of various time scales, film thicknesses, and substrate temperatures were made during deposition of gold and nickel films. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
1
31
1
Order By: Relevance
“…5,11,18 Although the exact mechanism for the fast reversible stress evolution has not been identified, a few important features are suggested by previous experimental observations. 7,9,13,15,18 (1) The mechanism leads to "reversible stress evolution" during a growth interruption and upon resumption. That is, as the growth is resumed, the stress rapidly returns to the pre-interruption stress evolution trajectory and continues as if the growth had never been stopped.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…5,11,18 Although the exact mechanism for the fast reversible stress evolution has not been identified, a few important features are suggested by previous experimental observations. 7,9,13,15,18 (1) The mechanism leads to "reversible stress evolution" during a growth interruption and upon resumption. That is, as the growth is resumed, the stress rapidly returns to the pre-interruption stress evolution trajectory and continues as if the growth had never been stopped.…”
mentioning
confidence: 91%
“…[13][14][15][16][17] Most recently, the stress evolution during a growth interruption has been shown to involve multiple kinetic processes, which can be interpreted as a fast reversible process and a slow irreversible process. 18 The slow process was shown to correspond to a process occurring in the bulk of the film and can be attributed mostly to grain growth after deposition. 5,11,18 Although the exact mechanism for the fast reversible stress evolution has not been identified, a few important features are suggested by previous experimental observations.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The stress relaxation was then argued to be the effect of out-diffusion of atoms from grain boundaries due to a reversal of the chemical potential difference when deposition is interrupted [77,78,95]. Experimental studies have reported that the stress relaxation upon interruption scales with the inverse grain size as predicted by the out-diffusion model [96] but that the stress relaxation does not have the temperature dependence predicted by a diffusion based relaxation process [97,98]. Others have suggested [81,99] that grain rotation coupled with grain boundary diffusion as a cause of the stress relaxation.…”
Section: Surface and Sub-surface Processes Leading To Stress Generatimentioning
confidence: 99%